Editorial - Quintero, Pablo (Cooperativismo & Desarrollo, 2016)
I am very pleased to have been invited by the esteemed journal Cooperativism & Development to write the editorial for this interesting issue. As is well known, Cooperativism & Development forms part of a distinguished core of publications charged with discussing and disseminating diverse experiences and research on the solidarity economy, so-called sustainable development, and, increasingly, what have been called “other economies”: alternative modes of production, exchange, and consumption standing in contrast to those following the epistemic and operational logic of capitalism. In essence, these economies stand in contrast to modern-colonial rationales.